2021
DOI: 10.1039/d0ew00985g
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of pharmaceutical contaminants by bubbling gas phase surface discharge plasma combined with g-C3N4 photocatalysis

Abstract: The gas phase surface discharge with microporous bubbling was used to evaluate the degradation feasibility of pharmaceutical contaminants. After 25 min treatment, 82% removal of ibuprofen (initial concentration of 60...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In view of this, several studies have been made using metal oxide and graphitic material related photocatalysts to make wastewater free from ibuprofen. 293–357…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this, several studies have been made using metal oxide and graphitic material related photocatalysts to make wastewater free from ibuprofen. 293–357…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 99%
“…Hernández-Uresti et al 333 observed the following order for the degradation of different pharmaceutical compounds in aqueous solution (pH ∼ 5.5) using g-C 3 N 4 under UV-vis irradiation: tetracycline (86%) > ciprofloxacin (60%) > ibuprofen (20%). Wang and coworkers 334 undertook investigations on the degradation of pharmaceutical contaminants by bubbling a gas-phase surface discharge plasma combined with g-C 3 N 4 photocatalysis. These findings disclosed 82% and 100% removal of ibuprofen and tetracycline hydrochloride after 25 min, corresponding to initial concentrations of 60 and 200 mg L −1 , respectively.…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 99%
“…33 Wang et al utilized a spiral electrode in a plexiglass cylinder to treat a 2 L solution of pharmaceutical contaminants, incorporating a gas pump and flow meter in a gas-phase surface discharge reactor for the gas supply system. 34 Zhou et al developed a microplasma bubble column reactor in which air from a gas cylinder was ionized in a plasma setup. Such a reactor effectively produces oxidative species, including…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a paper by Sun et al, a water falling film dielectric barrier discharge system was used for PAW production, where a gas pump facilitated the passage of ambient air through the discharge area at the upper end of a coaxial discharge cylinder, resulting in the treated solution flowing down as a uniform film along the ground electrode . Wang et al utilized a spiral electrode in a plexiglass cylinder to treat a 2 L solution of pharmaceutical contaminants, incorporating a gas pump and flow meter in a gas-phase surface discharge reactor for the gas supply system . Zhou et al developed a microplasma bubble column reactor in which air from a gas cylinder was ionized in a plasma setup.…”
Section: Introductionmentioning
confidence: 99%
“…When high-voltage electrons are introduced into a gas/liquid environment, gas molecules or atoms are ionized first to form initial radicals. Then, the generated radicals make contact and react with molecules in the liquid medium via the gas/liquid interface, leading to the generation of various radical species with high reactivity in the liquid phase. Based on the above advantages, gas/liquid discharge plasma has been applied in various fields, including dye treatment, , degradation of pharmaceutical compounds, , and synthesis of nanomaterials …”
Section: Introductionmentioning
confidence: 99%